Pilonidal Cyst of the Penis: Suggestion of a Management Plan Based on Literature Review and a Case Report - Kanafani, Ahmad; Hammoud, Ahmad; Bejjani, Noha; Mahfoud, Daniel; Youssef, Nazih (International Journal of Clinical Research, 2024)
Background: Pilonidal sinus rarely affects the penis. This disease is only discussed in case reports, around 26 cases in the literature, and never in textbooks or guidelines. Along with the scarce data in the literature, most of the reported cases were managed differently, and the diagnosis, which could only be confirmed with specimen histopathology, was delayed. Besides the case report of a rare penile disease, the purpose of this paper is to suggest a management plan for suppurative penile lesions to avoid delay in diagnosis and treatment. Case Report: We encountered a case of penile pilonidal sinus that was initially treated as an abscess based on an ultrasound result. The quick relapse and the suspicious second ultrasound of a hair-like septum in the lesion led to excision and histopathologic confirmation. Penile swelling in patients with a history of Papaverine or any vasoactive drugs injections, trauma, penile prosthesis, diabetes mellitus, intra-abdominal abscess, Tuberculosis, intravenous drug abuse, systemic symptoms, and signs of infection should be managed as an abscess; drainage, appropriate antibiotherapy, and management of risk factors and causes. Discussion: The usual clinical presentation of pilonidal disease of the penis consists of tender penile swelling, dyspareunia, and purulent discharge, as well as erectile dysfunction which was reported in only one case. In contrast to penile abscess, the presentation usually includes a tender penile swelling, and systemic symptoms such as fever, chills, and night sweats. Physical examination of this patient revealed a non-specific tender, pus-pointing, and pus-containing lesion with mildly erythematous edges, located near the coronal sulcus Conclusion: Pilonidal cyst of the penis is a rare disease with delayed management in the literature because of misdiagnosis caused by confusion with penile abscess. Though ultrasound could narrow the differential diagnosis, the clinical presentation remains the cornerstone in differentiating between penile abscess and pilonidal sinus.